Efektivitas Penegakan Hukum Terhadap Tindak Pidana Money Politik di Bawaslu Kabupaten Gorontalo - Stepi Ayu; Rustam Hs. Akili; Roy Marthen Moonti; Muslim A. Kasim (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem of election violations in the form of money politics continues to be a challenge in the democratization process in Indonesia, including in Gorontalo Regency. Although regulations have been strictly regulated in Law Number 7 Year 2017, the implementation of law enforcement against money politics still faces various obstacles. This study aims to analyze the obstacles faced by law enforcement officials, especially the Election Supervisory Agency (Bawaslu), in taking action against money politics violations during the implementation of the General Election in Gorontalo Regency. This type of research is empirical juridical research, with a qualitative approach and using interview techniques with Bawaslu commissioners as the main data source. The main findings show that the main obstacles come from weak evidentiary instruments, a deeply rooted transactional political culture in the community, and Bawaslu's limited authority in the law enforcement process. In addition, the lack of public participation in reporting violations is a factor that contributes to weakening the effectiveness of law enforcement. The conclusion of this study confirms that the success of law enforcement against money politics is largely determined by the synergy between strong regulations, independent and professional supervisory institutions, and public political awareness. Therefore, it is recommended that strengthening the institutional capacity of Bawaslu, reformulating regulations regarding the proof of money politics violations, and increasing public political education be prioritized in the electoral reform agenda in the regions.